Task Force on Scaling: Achieving widespread adoption of innovations from agricultural research - Deutsche Gesellschaft für Internationale Zusammenarbeit (Deutsche Gesellschaft für Internationale Zusammenarbeit, 2018)
Bringing research products into smallholder practice is by no means a new endeavour, but doing it on this scale is. Few initiatives have so far managed to conduct ‘scaling’ systematically and successfully. To support CGIAR and the World Vegetable Center in delivering on their strategic goals, the Deutsche Gesellschaft für Internationale Zusammenarbeit (GIZ) GmbH, on behalf of the German Federal Ministry for Economic Cooperation and Development (BMZ), launched the Task Force on Scaling to bring innovations from research into use on a massive scale. The understanding of the Task Force is that in order to contribute meaning-fully to CGIAR’s development outcomes, radical new thinking on the delivery and design of innovation is required. In pursuit of this mission, the Task Force explores new horizons, inspired by ambitious en-deavours such as launching rockets to reach distant planets in our solar system.